CONFLICT OF LAW ASPECTS OF SAME-SEX PARTNERSHIP CONCLUDED ABROAD: SOME REMARKS FROM THE ASPECT OF DOMESTIC PRIVATE INTERNATIONAL LAW - Pavlović, Mina (Pravni zapisi, 2022)
Registered partnership is not regulated in the Serbian legal system, norare there special conflict of law rules for this institute in the Law on resolvingconflict of laws with regulations of other countries (the Serbian PILAct). Therefore a question of conflict of law treatment of foreign registeredpartnership in the Serbian private international law is raised. In order todiscover adequate conflict of law rule for determination of applicable lawfor the termination, personal and property effects of this relationship, theauthor examines if it is possible to do that through qualification or throughcreation of a new conflict of law rule in accordance with Article 2 of thePIL Act, which regulates filling the legal gaps. The author also points out tosome conflict of law aspect of same-sex relationship (registered partnership)in cases with foreign element, if it is legalized in the Serbian legal system.
Keywords: same-sex relationships; registered partnership; international jurisdiction; same-sex union; qualification; conflict of law rule; filling the legal gap; (Serbian PIL Act); the Proposal of Same-sex union Act’s Draft